2020
DOI: 10.7717/peerj.9568
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive profile of risk factors for cardiovascular diseases using WHO STEP wise approach in Madhya Pradesh

Abstract: Background Periodic information on risk factor distribution is critical for public health response for reduction in non-communicable disease (NCDs). For this purpose, the WHO has developed STEPs wise approach. State representative population-based STEPS survey was last conducted in 2007–08 in seven states of In India. Since then no such work has been reported from low ETL states. This survey was carried out to assess the prevalence of risk factors associated with NCDs and the prevalence of NCDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…A total of 18.7% (95% CI [15.4–22.5]) were either overweight or obese, 22.3% (95% CI [20.5–24.1]) had raised blood pressure, 6.8% (95% CI [5.6–8.3]) had raised blood glucose, and 4.3% (95% CI [3.4–5.3]) had raised cholesterol levels. The detailed overall results are described in a previous publication ( Kokane et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 18.7% (95% CI [15.4–22.5]) were either overweight or obese, 22.3% (95% CI [20.5–24.1]) had raised blood pressure, 6.8% (95% CI [5.6–8.3]) had raised blood glucose, and 4.3% (95% CI [3.4–5.3]) had raised cholesterol levels. The detailed overall results are described in a previous publication ( Kokane et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…All the data was collected digitally using mobile phone-based applications, and securely stored prior to analysis. The methods of primary data collection, and overall results are described in detail elsewhere ( Kokane et al, 2020 ). Briefly, field investigators calculated the sampling interval for household selection in a cluster by dividing the total number of households in that cluster by 58.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that prevalence to be 25.7% in urban and 20.8% in rural areas. 2 These numbers translate into more than 200 million individuals with hypertension in India. 3 Given this huge burden, National Program for Cancer, Diabetes, Cardiovascular diseases and Stroke (NPCDCS) launched by the government of India envisages annual screening for hypertension in all adults above 30 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…We found that 22.3% of all individuals had hypertension, but only 11.8% were on some medication. 2,3 The proportion of those controlled is likely to be only about half of those on medication. In order to improve control, availability and access to quality health-care is imperative, in order to reduce cardiovascular mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%